The Japanese American internment : an interactive history adventure - Hanel, Rachael (Mankato, Minn. : Capstone Press, 2008)
"Describes the events surrounding the internment of Japanese Americans in relocation centers during World War II. The reader's choices reveal the historical details from the perspective of Japanese internees and Caucasians"--Provided by publisher.
"3 story paths, 43 choices, 11 endings"--Cover.
0700L
Keywords: Japanese Americans -- Evacuation and relocation -- 1942-1945; World War -- Japanese Americans -- 1939-1945; World War -- 1939-1945